Credit constraints and the measurement of time preferences - Mark Dean; Anja Sautmann (Brown University, Department of Economics, 2014)
Incentivized experiments are commonly used to estimate marginal rate of intertemporal substitution (MRS) in the lab and in the field, and to make inferences about subject's time preference. This paper considers the implications of an integrated model of behavior in which individuals are subject to financial shocks and credit constraints and take those into account when making experimental choices. The model shows that measured MRS depends on the individual's effective interest rate and her marginal utility of current and future consumption. Experimental responses should therefore be correlated with other variables that describe the subject's financial situation, like savings, income and consumption shocks. We test the model with a panel data set from Mali and find evidence for such effects. We discuss how our model can be combined with repeated time preference measures to identify time preferences and other household characteristics - including credit constraints and the importance of different types of financial shocks.
Keywords: 330